2021
DOI: 10.3390/cancers13092227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Neurofilament Light Chain and Glial Fibrillary Acidic Protein as Screening and Monitoring Biomarkers for Brain Metastases

Abstract: We evaluated the potential serum neurofilament light chain (sNfL) and serum glial fibrillary acidic protein (sGFAP) roles in diagnosing and monitoring brain metastases (BMs). We included 70 patients with newly diagnosed BMs, 71 age- and cancer type-matched patients without BMs, and 67 healthy controls (HCs). We compared sNfL and sGFAP levels among the groups using a single-molecule array immunoassay. We prospectively followed 26 patients with BMs every 2–3 months by measuring sNfL and sGFAP levels and performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Several publications have thus focused on the use of NfL as a diagnostic and prognostic blood marker. High blood levels of NfL in brain metastases (Hepner et al, 2019 ; Kim et al, 2021 ; Lin et al, 2022 ) was reported, these levels being correlated with the number and size of metastases (Lin et al, 2022 ). A decrease in levels of NfL was also detected following treatment (Kim et al, 2021 ).…”
Section: Nfl and Neurological Damagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications have thus focused on the use of NfL as a diagnostic and prognostic blood marker. High blood levels of NfL in brain metastases (Hepner et al, 2019 ; Kim et al, 2021 ; Lin et al, 2022 ) was reported, these levels being correlated with the number and size of metastases (Lin et al, 2022 ). A decrease in levels of NfL was also detected following treatment (Kim et al, 2021 ).…”
Section: Nfl and Neurological Damagesmentioning
confidence: 99%
“…For metastases diagnosis, NfL threshold values may be defined according to age: for example, NfL levels >22 pg/ml (measured by the Simoa approach) in cancer patients aged 51–60 years may predict the presence of brain metastases (Kim et al, 2021 ). Other biomarkers are also being evaluated, in particular the GFAP protein which would, according to Darlix et al ( 2021 ) outperform NfL as a diagnostic and prognostic factor for brain metastases in breast cancer patients.…”
Section: Nfl and Neurological Damagesmentioning
confidence: 99%
“…Moreover, disruptions in the blood–brain barriers may allow GFAP or NfL to cross through CSF to circulation. Previous studies have demonstrated that sNfL and sGFAP levels are associated with the number and size of BM lesions [ 13 , 15 ]. The diagnostic performance of sNfL and sGFAP is better in patients with symptomatic BM than in those without symptoms [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that sNfL and sGFAP levels are associated with the number and size of BM lesions [ 13 , 15 ]. The diagnostic performance of sNfL and sGFAP is better in patients with symptomatic BM than in those without symptoms [ 15 ]. Previous findings have demonstrated that elevated sNfL and sGFAP levels at the time of BM diagnosis were associated with poor patient outcomes [ 13 , 14 ], which can be explained by the association between sNfL and sGFAP levels and the extent of BM lesions; thus, the more advanced the BM, the worse the prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation